Island Migration, Resource Use, and Lithic Technology by Anatomically Modern Humans in Wallacea - Ono, Rintaro (Archīum Ateneo, 2020)
Island migration and adaptation including both marine and terrestrial resource use and technological development by anatomically modern humans (AMH) are among the most significant issues for Pleistocene archaeology in Southeast Asia and Oceania; and directly related to the behavioural and technological advancements by AMH. This paper discusses such cases in the Wallacean islands; located between the past Sundaland and the Sahul continent during the Pleistocene. The Pleistocene open sea gaps between the Wallacean islands and both landmasses are very likely the major factor for the relative scarcity of animal species originating from Asia and Oceania and the high diversity of endemic species in Wallacea. They were also a barrier for hominin migration into the Wallacean islands and Sahul continent. We summarise three recent excavation results on the Talaud Islands; Sulawesi Island and Mindoro Island in Wallacea region and discuss the evidence and timeline for migrations of early modern humans into the Wallacean islands and their adaptation to island environments during the Pleistocene.